PENGARUH KONSENTRASI IBA TERHADAP KEMAMPUAN BERAKAR SETEK PUCUK Alstonia scholaris (L.) R. Br. SEBAGAI UPAYA PENYEDIAAN BIBIT UNTUK REVEGETASI - Tiara, Tiara; Noli, Zozy Aneloi; Chairul, Chairul (Metamorfosa: Journal of Biological Sciences, 2017)
Alstonia scholaris (L.) R. Br. is an indigenous plant species in Indonesia which has been use for multiple purposes. This plant tolerant to poor nutrient and alkaline soil, therefore it is potential to explore as a revegetation plant. The study was conducted to identify effect of IBA concentrations on rooting ability of A. scholaris shoot cutting. Plant materials (shoot cutting) were collected from trubusan in Mandeh Area, Tarusan, West Sumatra. This study used Completely Randomized Design (CRD). The treatment was IBA concentrations (0 ppm, 50 ppm, 100 ppm, 150 ppm and 200 ppm). The result showed that IBA concentrations was significant different (P ? 0,05) for length, fresh weight and dry weight of root. The application of 150 ppm IBA was the best concentration to enhance the rooting ability of A. scholaris shoot cuttings.
Keywords: Alstonia scholaris, IBA, rooting ability, shoot cutting